2018
DOI: 10.1080/10826084.2018.1517798
|View full text |Cite
|
Sign up to set email alerts
|

More than just Alcohol: Marijuana and Illicit Drug Use at Parties Attended by 15–20 Year Olds

Abstract: Background Parties are a common setting for marijuana and illicit drug use among adolescents. Objectives This study examined the context of parties with alcohol, marijuana and illicit drug use attended by adolescents and young adults. Methods In 2016, an address-based sample of 1,764 15–20-year-olds in 24 U.S. communities participated in an online survey. Parties were categorized as alcohol-only (Alc-only), marijuana+alcohol (Mj+Alc), and illicit+marijuana+alcohol (ID+Mj+Alc) based on survey participants’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Six characteristics of the last party the participant attended were assessed (Egan et al., ). (i) Location of the party: One item asked “ For the last party you attended where alcohol was being served, where did it mostly take place?”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six characteristics of the last party the participant attended were assessed (Egan et al., ). (i) Location of the party: One item asked “ For the last party you attended where alcohol was being served, where did it mostly take place?”.…”
Section: Methodsmentioning
confidence: 99%
“…Risk for underage alcohol use and consequences varies across these factors, and drinking contexts are associated with the risk of experiencing alcohol‐related problems independent of an individual's level of alcohol consumption (Lipperman‐Kreda et al., ; Mair et al., ). For example, parties are the most commonly reported context for alcohol use among high school seniors (McCabe et al., ), and larger parties are associated with increased risk for drinking (Egan et al., ; Lipperman‐Kreda et al., ; Wagoner et al., ). Factors within these contexts may translate into increased risk for alcohol consumption and negative consequences by increasing access to alcohol (Bersamin et al., ), direct modeling of alcohol use behaviors (Clapp and Shillington, ), and reinforcing social norms and increasing social pressure to consume alcohol (e.g., Elek et al., ).…”
mentioning
confidence: 99%
“…Due to the focus of the parent study's objective to evaluate a comprehensive set of strategies, including social host ordinances, selected and implemented by community organizations, to be eligible, cities had to have a population between 25,000 and 300,000, a local law enforcement authority, and an active community substance abuse prevention coalition with leadership that was willing to participate in the trial. In addition, at the time of recruitment cities could not have a social host ordinance or be located within a state with a state-level social host law (Egan et al, 2018;Wolfson et al, 2017). Social host laws and ordinances hold property owners, or those who control the property, liable for underage drinking that occurs on the property (Wagoner et al, 2011).…”
Section: Community Recruitmentmentioning
confidence: 99%
“…SAM use among youth and young adults frequently occurs in a social context (Terry McElrath et al, 2013). In a sample of 15-20 year olds residing in the US who had ever attended a party with alcohol, 24.9% reported that they had observed both alcohol consumption and marijuana use at the last party they attended (Egan et al, 2018). Parties where both alcohol and marijuana were used were more likely than parties with just alcohol consumption to occur in someone else's home, be larger in size with the majority of attendees under 21, and in a state where medical and recreational marijuana were legal (Egan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation